The endangered self : managing the social risk of HIV - Green, Gill, 1956-; Sobo, Elisa Janine, 1963- (Health, risk and society., 2000)
"To date, the majority of HIV/AIDS research has concentrated on education and prevention for those with a seronegative status, and studies of HIV positive individuals have been concerned with their potential to infect others. The Endangered Self, however, focuses on how the discovery of an HIV-positive status affects the individual's sense of identity and on the experience of living with HIV, and its effects on the individual's social relationships." "Drawing upon the concepts of stigma, dangerous identities, and health risk, the authors describe the revaluation that people living with HIV and AIDS must make of the risks entailed by everyday social interactions, and examine their negotiation of these interactions. In this study, which combines a UK/US perspective, Green and Sobo explore identity change and the stigma attached to an HIV-positive status within the context of the sociology of risk."--Jacket.